S2P: A software tool to quickly carry out reproducible biomedical research projects involving 2D-gel and MALDI-TOF MS protein data. (March 2018) - López-Fernández, Hugo; Araújo, José E.; Jorge, Susana; Glez-Peña, Daniel; Reboiro-Jato, Miguel; Santos, Hugo M.; Fdez-Riverola, Florentino; Capelo, José L.
Highlights: S2P, a multiplatform application for the integrated analysis of 2D-gel and MALDI-based mass spectrometry protein data is presented. Our software provides different functionalities to process 2D-gel and MALDI-mass spectrometry protein identification-based data in a computer-aided, reproducible manner. S2P incorporates a user-friendly, intuitive graphical user interface (GUI), designed for biomedical researchers without advanced bioinformatics skills. S2P reduces the time that researchers need to invest in order to prepare data for subsequent analysis, such as discovering potential biomarkers. Different case studies demonstrate the usefulness of S2P. Abstract: Background and objective: 2D-gel electrophoresis is widely used in combination with MALDI-TOF mass spectrometry in order to analyze the proteome of biological samples. For instance, it can be used to discover proteins that are differentially expressed between two groups (e.g. two disease conditions, case vs. control, etc.) thus obtaining a set of potential biomarkers. This procedure requires a great deal of data processing in order to prepare data for analysis or to merge and integrate data from different sources. This kind of work is usually done manually (e.g. copying and pasting data into spreadsheet files), which is highly time consuming and distracts the researcher from other important, core tasks. Moreover, engaging in a repetitive process in a non-automated, handling-based manner is prone to error, thus threatening reliability and reproducibility. The objective of this paper is to present S2P, an open source software to overcome these drawbacks. Methods: S2P is implemented in Java on top of the AIBench framework, and relies on well-established open source libraries to accomplish different tasks. Results: S2P is an AIBench based desktop multiplatform application, specifically aimed to process 2D-gel and MALDI-mass spectrometry protein identification-based data in a computer-aided, reproducible manner. Different case studies are presented in order to show the usefulness of S2P. Conclusions: S2P is open source and free to all users athttp://www.sing-group.org/s2p . Through its user-friendly GUI interface, S2P dramatically reduces the time that researchers need to invest in order to prepare data for analysis.